Efficacy and tolerability of pramipexole for the treatment of primary restless leg syndrome: a meta-analysis of randomized placebo-controlled trials - Zhang W (Dove Medical Press, 2013)
Wei Zhang, Ye Wang, Shu Yan Cong, Jian Fei Nao, Juan Feng, Guo Rong Bi Neurology Department, Shengjing Hospital of China Medical University, Shenyang, People’s Republic of China Abstract: Primary restless leg syndrome (RLS) is a common sensory-motor disorder that is characterized by an irresistible urge to move the limbs and unpleasant sensations in the legs, which affects 1.9%–4.6% adults. Pramipexole, a potent dopamine D2/3 agonist, is recommended as “effective” in the short-term and “possibly effective” in the long-term treatment of primary RLS in the European guidelines on management of RLS. In this meta-analysis, we summarized the efficacy and tolerability of pramipexole in treatment for primary RLS. Results of this meta-analysis showed a favorable effect of pramipexole versus placebo on RLS symptoms (mean change on International RLS Study Group Rating Scale [IRLS] score: mean difference [MD] = -5.96; 95% confidence interval [CI]: -7.79 to -4.41, P < 0.00001) and sleep quality (pooled standard mean difference [SMD] = -0.48, 95% CI: -0.61 to -0.35, P < 0.00001). Nausea (relative risk [RR] = 2.68, 95% CI: 1.82 to 3.95, P < 0.001) and fatigue (RR = 1.82, 95% CI: 1.14 to 2.93, P = 0.013) were the most common adverse events, but, by and large, pramipexole was well-tolerated in patients with primary RLS. Nevertheless, long-term studies and more evidence of head-to-head comparisons of pramipexole with other dopamine agonists, anticonvulsants, and levodopa are needed. Keywords: restless legs syndrome, pramipexole, meta-analysis